INNOVATIVE STRATEGIES FOR THE EDUCATIONAL PROCESS: WORLD EXPERIENCE - Лузік, Е.; Дибкова, Л.; Кокарєва, А.; Хоменко-Семенова, Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The research is devoted to the problem of innovative strategies in education, in particular, the structure, forms and methods of teaching. An analysis of national and international strategies covering innovation in education as a system that promotes the development of innovative skills in the economy and society, namely the development of critical thinking, creativity and creativity, in addition to strong subjective, social and emotional skills that is the key to the success of innovation. Innovation skills are divided into three categories: thematic skills that represent knowledge and know-how in a particular field; thinking and creativity, including both higher-level skills and creative-cognitive (these competences include critical abilities, imagination and curiosity); Behavioral and social skills, including skills such as self-confidence, leadership and governance, collaboration and belief. The study concluded that: contrary to the common opinion, education is not an innovative idea: the volume of changes in education can be compared with similar public sectors; Unfortunately, education, unfortunately, was unable to use technology to increase productivity, innovation policy in education often focuses on fragmented issues or misplaced goals, sometimes due to the fear of quick victories, but without sustainable benefits in the long run; although innovation in education is not synonymous with the introduction of digital technologies, innovation strategies must include smart introduction and use of technologies in a way that uses their potential for better teaching and learning practices; effective innovative education strategies should include an appropriate management model; Innovation in education needs a strong assessment. Without a widespread and widespread culture, the assessment of innovation in education will remain at the level of well thought out but isolated innovative efforts; education also has a key relation to innovation in general: as a system that develops the skills of innovation in the economy and society